The Effect of Employee Placement and Work Discipline on Employee Performance at PAM Tirta Kamuning, Kuningan Regency - Septiani, Zihan Fadila; Hartono, Edy; Wibowo, Sandi Nasrudin (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2021)
This study aims to determine the effect of employee placement and work discipline on employee performance. The type of research used is quantitative research. And using the associative method to determine the relationship between employee placement variables and work discipline on employee performance. The subjects of this study amounted to 182 people, so the determination of the sample in this study used probability sampling with the slovin technique so that a sample of 65 people was obtained. With the aim of respondents being division heads, branch heads, and staff on duty at PAM Tirta Kamuning, Kuningan Regency. The instrument uses 5 Likert scale. The analysis used is multiple regression test to find out how much influence employee placement and work discipline have on employee performance, with the help of SPSS 22.0 for Windows.3,570. Work discipline has a positive and significant effect on employee performance with a significant value of 0.000 and t count of5.584. Employee placement and work discipline together have a significant effect on employee performance with a significant value of 0.000 and f count of 77.950.